IFABP levels predict visceral malperfusion in the first hours after open thoracoabdominal aortic repair - Doukas, Panagiotis; Bassett, Cathryn; Krabbe, Hanif; Frankort, Jelle; Jacobs, Michael J.; Elfeky, Moustafa; Gombert, Alexander (Frontiers in Cardiovascular Medicine, 2023)
Introduction Intestinal ischemia after open thoracoabdominal aortic repairs, is a rare but devastating complication, associated with high mortality. Notoriously challenging to diagnose, visceral malperfusion necessitates immediate surgical attention. Intestinal fatty acid-binding protein (IFABP) has been proposed as a biomarker for the diagnosis of intestinal wall damage. In this prospectively conducted, observational study we evaluated the diagnostic capacity of IFABP levels in patients' serum and their correlation with visceral malperfusion. Methods 23 patients undergoing open thoracoabdominal aortic repairs were included in this study and 8 of them were diagnosed postoperatively with visceral malperfusion—defined as a partial or complete thrombotic occlusion of the superior mesenteric artery and/or the coeliac trunk. IFABP levels and laboratory parameters often associated with intestinal ischemia (leucocytes, CRP, PCT and lactate) were measured at baseline, directly postoperatively, and at 12, 24 and 48 h after surgery. Postoperative visceral malperfusion—as revealed in CT angiography—was assessed and the predictive ability of IFABP levels to detect visceral malperfusion was evaluated with receiver-operator curve analysis. Results Patients with visceral malperfusion had a relevant risk for a fatal outcome (p = .001). IFABP levels were significantly elevated directly postoperatively and at 12 h after surgery in cases of visceral malperfusion. High IFABP concentrations in serum detected visceral malperfusion accurately during the first 12 h after surgery, with the maximum diagnostic ability achieved immediately after surgery (AUC 1, Sensitivity 100%, Specificity 100%, p < .001). Conclusion We conclude, that IFABP measurements during the first postoperative hours after open thoracoabdominal aortic surgery can be a valuable tool for reliable and timely detection of visceral malperfusion.